Masalah Cina : Konflik Etnis yang Tak Kunjung Selesai - Thung Ju Lan (Antropologi Indonesia, 1999)
The May riot of 1998 has brought the so-called Chinese problem to the forefront. Various comments on the problem are mostly based on memories of the past, of the Dutch colonial segregation policy, and the common perception of the present conflict. The latter refers to the social economic gap between the Indonesian Chinese and the indigenous Indonesians. However, none of these comments address to the core of the problem related to the ethnicity and nationalism. The problem emerged when ethnicity and nationalism were in conflict. This conflict began with the establishment of the modern (Indonesian) nation-state. Since the beginning, the basis for discrimination between the indigenous and non indigenous has legally been set up by the 1945 constitution (article no.26). This discrimination was strengthened by the new order's policy that assimilation in the sole route to solving the so-called Chinese problem. This policy has produced wider social cultural, economic, and political gaps between the Indonesian Chinese and the indigenous Indonesian. The situation has developed in such a way that to solve the problem a careful examination using a multidisciplinary approach that pays attention to spatial and temporal variation in necessary.